2007
DOI: 10.1097/bot.0b013e31803071da
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Orthopaedic Implants by Airport Metal Detectors

Abstract: Prostheses, plates of length >10 holes, and titanium nails were the best predictors of detection by the arch. These 3 factors accounted for 42 of the 43 detections by the arch. Body mass index was not shown to affect detectability of orthopaedic implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 5 publications
1
14
0
3
Order By: Relevance
“…We do, however, offer a ''real world'' report of the experience of these 90 children and adolescents, thus providing information to surgeons and patients about a commonly asked question, for which very limited data exists. Post-9/11 reports in the arthroplasty [4,[6][7][8][9][10] and trauma [8][9][10] literature have indicated triggering rates ranging from 32 to 84 % that is affected by metal composition and total implant mass. The only recent report of spinal instrumentation evaluated several types of titaniumonly implants in 40 patients and noted no metal detector triggering in a British cohort [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do, however, offer a ''real world'' report of the experience of these 90 children and adolescents, thus providing information to surgeons and patients about a commonly asked question, for which very limited data exists. Post-9/11 reports in the arthroplasty [4,[6][7][8][9][10] and trauma [8][9][10] literature have indicated triggering rates ranging from 32 to 84 % that is affected by metal composition and total implant mass. The only recent report of spinal instrumentation evaluated several types of titaniumonly implants in 40 patients and noted no metal detector triggering in a British cohort [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to heightened security measures, previous studies have indicated that both metallurgy [9,10] and implant mass [2,4,6,8,10] also affect detector activation. To date, however, nearly all of these reports have been in adult patients with trauma instrumentation (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that larger plates with more than 10 holes, used in orthopaedic surgery, may be more detectable. 8 Breast implants incorporating metallic components to allow for expansion are in common use. Neither of the two commonly used expanders in our unit activated the arch metal detector, nor were they detected by the wand when placed under the arm.…”
Section: Wand Detectormentioning
confidence: 99%
“…1 The amplitude of the electrical current in the receiver coil should be greater in ferromagnetic metals with a high iron content than in electrically conducting diamagnetic metals such as copper, aluminium, titanium, gold or silver. 8 The newer implants are frequently highly refined alloys such as titanium, cobalt-chromiummolybdenum and stainless steel. As such, they tend to have low iron content 9 and are therefore less likely to be detected.…”
Section: Wand Detectormentioning
confidence: 99%